2022
DOI: 10.3390/ani12172223
|View full text |Cite
|
Sign up to set email alerts
|

Wild Carnivore Survey of Echinococcus Species in Slovenia

Abstract: Wild carnivores are definitive hosts and potential reservoirs for the tapeworm Echinococcus sp. which can cause cystic and alveolar echinococcosis. Both are considered neglected and important food-borne pandemics. This study is the first to molecularly test Slovenian wild carnivores for Echinococcus species that can cause disease in humans. Fecal samples from 210 red foxes (Vulpes vulpes), 42 wolves (Canis lupus), 39 golden jackals (Canis aureus), 18 martens (Marten sp.), 2 Eurasian lynx (Lynx lynx), 2 Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The high County prevalence of HAE in Bjelovar-Bilogora County is in accordance with a high observed County prevalence among red foxes of 28.57% recorded in 2018. As in Croatia, in the neighboring countries, a rise in E. multilocularis infection prevalence among red foxes has been observed: in Slovenia, it increased from 2.6% (2010) [ 13 ] to 29.1% (2019–2022) [ 14 ]. In Hungary, the mean prevalence of red foxes gradually increased, and it was 5%, 10.7%, 7.9%, and 12.5% in 2002, 2008–2009, 2012–2013, and 2018–2020, respectively [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high County prevalence of HAE in Bjelovar-Bilogora County is in accordance with a high observed County prevalence among red foxes of 28.57% recorded in 2018. As in Croatia, in the neighboring countries, a rise in E. multilocularis infection prevalence among red foxes has been observed: in Slovenia, it increased from 2.6% (2010) [ 13 ] to 29.1% (2019–2022) [ 14 ]. In Hungary, the mean prevalence of red foxes gradually increased, and it was 5%, 10.7%, 7.9%, and 12.5% in 2002, 2008–2009, 2012–2013, and 2018–2020, respectively [ 15 , 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis from 2016 showed the highest pooled prevalence of the parasite among red foxes in Baltic and central European countries of 58.0, 36.8, 34.9, 29.2 and 27.3% in Lithuania (2001Lithuania ( -2006, Latvia (2002Latvia ( -2008, Liechtenstein (1990Liechtenstein ( -1992, Germany (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) and Slovakia (2000Slovakia ( -2013, respectively [21]. Recent animal data from neighboring Slovenia [14] and data from Bjelovar-Bilogora County from this study, where parasite prevalence among examined red foxes in the observed regions reached nearly 30%, clearly show the spread of this infection in the main host; this has resulted in the local emergence of HAE cases in central continental Croatia. The low disease incidence and unfamiliarity of healthcare workers with alveolar echinococcosis have contributed to initial misdiagnosis in a substantial proportion of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Foxes, belong to the canid family and are the most numerous predator species found throughout Croatia [4]. According to many authors, they serve as potential reservoirs for a wide range of infectious diseases and zoonotic pathogens, including the rabies virus, Trichinella spp., Echinococcus spp., Leptospira [4,5,28,29], and Salmonella spp. [30].…”
Section: Discussionmentioning
confidence: 99%
“…A broad home range, territorial mobility, a highly unselective diet and behavioral features predispose golden jackals to many infectious agents, including parasites. As noted with Echinococcus multilocularis [26], golden jackals may play a significant role in the dissemination of clinically important parasites, which warrants more extensive investigation. There is no report on the presence of N. caninum in their feces, although seropositive golden jackals were reported from Israel [27,28].…”
Section: Introductionmentioning
confidence: 97%